Penentuan Sektor dan Sub Sektor Pertanian Unggulan Di Kabupaten Tulungagung: The Determination of Agricultural Leading Sector and Sub Sectors in Tulungagung Regency - Sazali, Ferdian; Sugiyarto (Jurnal Riset Agribisnis dan Peternakan, 2025)
This study aims to (1) identify the development trends of the agriculture, forestry, and fisheries sectors and subsectors in Tulungagung Regency; (2) examine the role of the agriculture, forestry, and fisheries sectors and subsectors in the economy of Tulungagung Regency; and (3) analyze the economic patterns and structures of these sectors and subsectors in Tulungagung Regency. The research was conducted in Tulungagung Regency, East Java Province. The area selection in this study was carried out using a purposive sampling method. The analytical methods used include trend analysis, Location Quotient and Dynamic Location Quotient, as well as Klassen Typology analysis. The results of the study show that (1) the trend in the agriculture sector and subsectors tends to increase; (2) the agriculture, forestry, and fisheries sector, as well as the agriculture, livestock, hunting, and agricultural services subsector, serve as potential base sectors; and (3) the agriculture, forestry, and fisheries sector, along with the agriculture, livestock, hunting, and agricultural services subsector, are classified as advanced but pressured sectors